New Roots for Ecological Intensification. Issue 11 (29th October 2014) - Crews, Timothy; Cox, Thomas; De Haan, Lee; Damaraju, Sivaramakrishna; Jackson, Wes; Nabukalu, Pheonah; Van Tassel, David; Wang, Shuwen
Abstract : This month, ASA, CSSA, and SSSA have teamed up with the American Society of Agricultural and Biological Engineers (ASABE) to produce a joint issue under the theme "Feeding the World in 2050." More than 20 articles were written on various topics addressing the challenges we face in feeding the world, a handful of which appear in this issue of CSA News magazine (for the full presentation, please see ASABE's Resource magazine here: www.asabe.org/publications/resource‐magazine.aspx ). In addition to the joint articles, we also are including a profile this issue of the 2014 World Food Prize winner, Sanjaya Rajaram, a Fellow of ASA and CSSA .